The potential cost-effectiveness of HPV vaccination among girls in Mongolia. (August 2022) - Luvsan, Munkh-Erdene; Vodicka, Elisabeth; Jugder, Uranbolor; Tudev, Undarmaa; Clark, Andy; Groman, Devin; Otgonbayar, Dashpagam; Demberelsuren, Sodbayar; LaMongtagne, D. Scott; Pecenka, Clint
Abstract: Introduction: Cervical cancer is a leading cause of cancer among women in Mongolia with an age-standardized incidence rate of 23.5 per 100, 000. HPV vaccination has not been introduced nationally and Gavi co-financing support is not available in Mongolia. Extended Gavi pricing for HPV vaccine may be available from vaccine manufacturers for a number of years. To inform introduction decision-making, we evaluated the potential cost-effectiveness of HPV vaccination among girls and young women in Mongolia. Methods: We used UNIVAC (version 1.4), a static decision model, to evaluate the health and economic outcomes of single-cohort vaccination among females from the government perspective compared to no vaccination. We modeled vaccine introduction over 10 birth cohorts starting in 2022 comparing quadrivalent or bivalent vaccine selection and vaccine pricing variations. We used locally-specific data for cancer incidence, mortality, treatment and costs. Model outcomes included cancer cases, hospitalizations, deaths, disability-adjusted life years (DALY), and costs presented in 2018 USD. Incremental costs and health outcomes were discounted at 3% and aggregated into an Incremental Cost-Effectiveness Ratio (ICER). Results: The base-case scenario of HPV vaccination among 9 year-old girls was projected to avert 5, 692 cervical cancer cases, 3, 240 deaths, and 11, 886 DALYs and incur 2.4–3.1M more costs compared to no vaccination. At prices of (4.50-4.60/dose), we estimated an ICER of 166-265/DALY averted among 9-year-olds. When price per dose was increased to reported mean vaccine purchase price for non-Gavi LMICs (14.17/dose), the ICER ranged from 556–820/DALY averted. Conclusion: HPV vaccination among girls is highly likely to be a cost-effective investment in Mongolia compared to no vaccination with projected ICERs less than 20% of the 2018 GDP per capita of 3, 735.